The Success of Root Cuttings is Endangered Kalapi (Kalappia celebica Kosterm.) by Giving Rootone-F Growth Regulator - Febriyani Febriyani, Febriyani Febriyani; Faisal , Faisal Danu Tuheteru; Asrianti , Asrianti Arif; Husna, Husna Husna (Forestry Department, University of Muhammadiyah Makassar, 2021)
Kalapi (Kalappia celebica Kosterm.) is endemic in Sulawesi and Endangered species. Plant propagation needs to be done but is constrained by limited seeds. Vegetative propagation of plants can be an alternative method such as using the root cutting technique that has been done previously on other types of species. This study aims to determine the success of vegetative propagation of kalapi (K. celebica), an endangered tree species by root cuttings using Rootone F. as root growth regulator. The research took place from March to June 2019 conducted at the plastic house of the Indonesian Mycorrhizal Association (AMI) Southeast Sulawesi Branch, Kendari. This study used a Randomized Block Design (RBD) consisting of 6 treatments of Rootone-F concentration: (a) 0 ppm, (b) 100 ppm, (c) 200 ppm, (d) 300 ppm, (e) 400 ppm and (f) 500 ppm. Each treatment was repeated three times and three units of the plant so that the total experimental unit used was 54 units. The results showed that the provision of Rootone-F could increase the success of the growth of kalapi root cuttings. Rootone-F concentration of 500 ppm gives the best results on the percentage of cuttings, percentage of sprouts, percentage of roots, number of shoots and shoot dry weight. The results showed that kalapi can be propagated by root cuttings.